Attendance of the Body and its importance in existential Phoenomenology - Shker, Saleh; Sbeira, Faten (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research discusses the presence of the body and its importance in existential phoenomenological philosophy, based on the study of the historical extensions of the idea of ​​the body through modern Western philosophical awareness, in an attempt to identify the concept of the body and its cognitive and human dimensions. And by showing the real problem posed by existential philosophy, the problem of the relationship between "self" and "existence". And the body as the one who evaluates the self in existence, and to demonstrate the problem of the body in the phenomenological perception as a new horizon to transcend the dualism of the subject in modern philosophical thought, which contributed to reducing the chances of philosophical contemplation and physiognomy of the body; the research seeks to reveal the importance of the phenomological approach, The body of man has an essential role to play in shaping his own self-awareness and to reveal the important place of the body in French existentialism; by studying the body and understanding the meanings that it is associated with French philosophers, The physical body), but as the use of the body’s phenomenology and its relationship to the world, and to the individual’s self-perception of the body, from being a body bound to the presence of the body, being active and active in existence.